Sex differences in rats: Effects of chronic stress on sympathetic system and anxiety - Renard, Georgina Maria (2005)
In this study we tested whether periodic maternal deprivation (MD) (4.5 h daily during the first 3 weeks of life) caused chronic changes in anxiety and medullo-adrenal responses to chronic stress in either male or female adult (2.5 months of age) rats, or both. Repeated maternal deprivation had a sex-specific effect on epinephrine (E) and norepinephrine (NE) levels: an increase in both measures was observed only in females. Unpredictable stress did not produce changes on plasma catecholamine levels either in males or females. However, when the females were maternally deprived as well as stressed they showed an increase in plasma NE p < 0.05. On the other hand, non-maternally deprived (NMD), maternally-deprived and stressed males showed high levels of catecholamines compared to females p < 0.001. In the elevated plus maze test, MD-treated males displayed a slight increase in anxiety-related behavior compared with NMD rats. This was indicated by a reduction in the time spent on the open arms, whereas females showed less anxiety, indicated by an increase in the number of entries, and in the time spent on the open arms. After exposure to chronic stress only the females displayed decreased anxiety-related behavior. These results suggest that there are sex-induced effects in emotional reactivity, perception of the stressor and in the evaluation of novel situations. Thus, maternal deprivation and chronic variable stress caused both long-term alterations in sympathetic response and gender-dependent changes in the anxiety index of adult rats.